Evaluasi atas Sistem Informasi Akuntansi Pembelian dalam Kaitannya dengan Pengendalian Intern pada Perusahaan - Marlina, Tri; Happines, Tami (Jurnal Ilmiah Akuntansi Kesatuan, 2017)
Purchasing Accounting Information System is used in companies for procurements of required goods in production process. Purchasing can be grouped into 2 (two) sections, import and local. Purchasing Accounting Information System is necessary to be applied for the production sustainability. In this case, companies must set adequate control starting from vendor selection, material selection, until the materials arrive in the warehouse. This study is aimed at finding out the purchasing accounting information system operated in PT Citra Abadi Sejati Bogor, and to eamine whether there is a relationship with internal control. The results show thaht PT Citra Abadi Sejati has operated a proper purchasing accounting information system and in accordance with the Standard Operating Procedures and general standar by using a system called Movex. And so as the internal control also has been operated properly and adequately shown by the jobs separations, serial number-printed documents, and completed with necessary papers.